Fuel cells for homes and hospitals. - Wolk, R.H (IEEE spectrum)
Along with promising car and bus applications, fuel cells in stationary versions are being designed to power single homes and large buildings. Some systems gain more output power by operating the cell in combination with a gas turbine. The author discusses the basic principles of fuel cells and fuel processing technology. Fuel cells for residential applications and combined gas turbine/fuel cell systems are also discussed. The key to increased use of fuel cells is cost reduction at the production stage